First-passage time: a conception leading to superstatistics - Ryazanov, V.V.; Shpyrko, S.G. (Condensed Matter Physics, 2006)
To describe the nonequilibrium states of a system we introduce a new thermodynamic parameter – the lifetime (the first passage time) of a system. The statistical distributions that can be obtained out of the mesoscopic description characterizing the behaviour of a system by specifying the stochastic processes are written. Superstatistics, introduced in [Beck C., Cohen E.G.D., Physica A, 2003, 322A, 267] as fluctuating quantities of intensive thermodynamical parameters, are obtained from statistical distribution with lifetime (random time to system degeneracy) as thermodynamical parameter (and also generalization of superstatistics).